PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN PERSEPSI PELUANG KERJA TERHADAP TURNOVER INTENTION - Wulansari, Septi; Setiawati , Ira; Indriasari, Ika (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyze the effect of compensation, leadership style, work environment, and perceptions of job opportunities on employee turnover intention. The population used in this study were all employees working and the sample used is 70 employees. This study used non-probability sampling technique research methods with saturated sampling method (census). Data analysis in this study used the SPSS 24 program. The data analysis technique used was multiple linear regression analysis. The results of the analysis and discussion show that the variable Compensation has a partial negative effect on Turnover Intention, Leadership Style has a partial negative effect on Turnover Intention, Work Environment has a partial negative effect on Turnover Intention, and Perception of Work Opportunities has a partial positive effect on Turnover Intention.